Green synthesized montmorillonite/carrageenan/Fe3O4 nanocomposites for pH-responsive release of protocatechuic acid and its anticancer activity - Yew, Yen Pin; Shameli, Kamyar; Mohamad, S. E.; Lee, Kar Xin; Teow, Sin Yeang * (MDPI, 2020)
Discovery of a novel anticancer drug delivery agent is important to replace conventional cancer therapies which are often accompanied by undesired side e↵ects. This study demonstrated the synthesis of superparamagnetic magnetite nanocomposites (Fe3O4-NCs) using a green method. Montmorillonite (MMT) was used as matrix support, while Fe3O4 nanoparticles (NPs) and carrageenan (CR) were used as filler and stabilizer, respectively. The combination of these materials resulted in a novel nanocomposite (MMT/CR/Fe3O4-NCs). A series of characterization experiments was conducted. The purity of MMT/CR/Fe3O4-NCs was confirmed by X-ray di↵raction (XRD) analysis. High resolution transmission electron microscopy (HRTEM) analysis revealed the uniform and spherical shape of Fe3O4 NPs with an average particle size of 9.3 ± 1.2 nm. Vibrating sample magnetometer (VSM) analysis showed an Ms value of 2.16 emu/g with negligible coercivity which confirmed the superparamagnetic properties. Protocatechuic acid (PCA) was loaded onto the MMT/CR/Fe3O4-NCs and a drug release study showed that 15% and 92% of PCA was released at pH 7.4 and 4.8, respectively. Cytotoxicity assays showed that both MMT/CR/Fe3O4-NCs and MMT/CR/Fe3O4-PCA e↵ectively killed HCT116 which is a colorectal cancer cell line. Dose-dependent inhibition was seen and the killing was enhanced two-fold by the PCA-loaded NCs (IC50–0.734 mg/mL) compared to the unloaded NCs (IC50–1.5 mg/mL). This study highlights the potential use of MMT/CR/Fe3O4-NCs as a biologically active pH-responsive drug delivery agent. Further investigations are warranted to delineate the mechanism of cell entry and cancer cell killing as well as to improve the therapeutic potential of MMT/CR/Fe3O4-NCs.